2007
DOI: 10.1161/circresaha.107.160614
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycogen Synthase Kinase 3β During Heart Failure Is Protective

Abstract: Abstract-Glycogen synthase kinase (GSK)-3, a negative regulator of cardiac hypertrophy, is inactivated in failing hearts. To examine the histopathological and functional consequence of the persistent inhibition of GSK-3␤ in the heart in vivo, we generated transgenic mice with cardiac-specific overexpression of dominant negative GSK-3␤ (Tg-GSK-3␤-DN) and tetracycline-regulatable wild-type GSK-3␤. GSK-3␤-DN significantly reduced the kinase activity of endogenous GSK-3␤, inhibited phosphorylation of eukaryotic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 32 publications
6
108
0
Order By: Relevance
“…In addition, mitochondrial affinity for the anti-apoptotic protein Bcl-2 increased, with more Bcl-2 associated with mitochondria in the presence of GSK-3 inhibition, inferring a pro-apoptotic role for GSK-3. This conclusion is substantiated by the work of Hirotani et al, (83) On the other hand, Nishino et al, (86) using a mouse line lacking the critical N-terminal serine within myocardial GSK-3β (Ser9) as well as Ser21 in GSK-3β, still found protection via preconditioning in the isolated, perfused heart subjected to ischaemia, excluding a role for inhibition of GSK-3 in this phenomenon in the mouse heart as opposed to the findings of Juhaszova in the rat heart. (81) GSK-3 inhibition in the heArt -A tuG-of-WAr?…”
Section: Gsk-3 and Myocardial Cell Death Or Cell Survivalsupporting
confidence: 56%
“…In addition, mitochondrial affinity for the anti-apoptotic protein Bcl-2 increased, with more Bcl-2 associated with mitochondria in the presence of GSK-3 inhibition, inferring a pro-apoptotic role for GSK-3. This conclusion is substantiated by the work of Hirotani et al, (83) On the other hand, Nishino et al, (86) using a mouse line lacking the critical N-terminal serine within myocardial GSK-3β (Ser9) as well as Ser21 in GSK-3β, still found protection via preconditioning in the isolated, perfused heart subjected to ischaemia, excluding a role for inhibition of GSK-3 in this phenomenon in the mouse heart as opposed to the findings of Juhaszova in the rat heart. (81) GSK-3 inhibition in the heArt -A tuG-of-WAr?…”
Section: Gsk-3 and Myocardial Cell Death Or Cell Survivalsupporting
confidence: 56%
“…The role of GSK-3β in cardiac hypertrophy has been examined extensively by several groups, and the vast majority of studies have found that expression of either WT or a constitutively active S9A mutant repressed hypertrophy (8)(9)(10)(11)(12)(13)(14). However, based on studies with overexpression of a dominant inhibitory mutant of GSK-3β, which showed no enhancement of hypertrophy following TAC, it was not clear what role, if any, inhibition of GSK-3β played in the response (12). Findings with GSK-3α have been even less clear.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that all studies to date have used transgenesis, knockin of activated mutants, or nonselective small molecule inhibitors (e.g., BIO) (8)(9)(10)(11)(12)(13)(14). None of these strategies allow one to define the true biology of GSK-3s or an understanding of isoform-specific effects.…”
Section: Introductionmentioning
confidence: 99%
“…99 Apoptosis by these insults was suppressed by overexpression of the adrenomedullin gene 95 or kallikrein gene 96 or treatment with statins, 97 all of which induced phosphorylation of GSK-3β. Furthermore, this protection from apoptosis was inhibited by dominant-negative Akt or active GSK-3β mutant and mimicked by pharmacological inhibitors of GSK-3β.…”
Section: Role Of Gsk-3β In Apoptosis Of Cardiomyocytesmentioning
confidence: 99%